Tirukkur̲aḷ mūlam (akaravaricaippaṭi) - Tiruvaḷḷuvar,Mārkkacakāyañ Ceṭṭiyār, Va.,Irāmacāmip Pulavar, Cu. A. (Tirunelvēlit Ten̲n̲intiya Caivacittānta Nūr̲patippuk Kal̲akam Limiṭeṭ, 2019)
Alphabetically arranged Tirukkur̲aḷ, ancient Tamil didactic verse work, by Tiruvaḷḷuvar with thematic dictionary
Keywords: Tiruvaḷḷuvar; Tirukkur̲aḷ; Didactic poetry; Tamil; Tamil poetry